2019
DOI: 10.1186/s12917-019-1955-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of Korean native goats (Capra aegagrus hircus) with bovine viral diarrhea virus 1b

Abstract: Background Bovine viral diarrhea virus (BVDV) infects various ungulates and causes reproductive failure in infected goats. BVDV has been detected among goats in the Republic of Korea, but the route of transmission remains unclear. Here, we aimed to investigate whether BVDV-1b circulating among Korean cattle can be transmitted to Korean native goats ( Capra aegagrus hircus ) and characterize the outcomes of BVDV infection in these goats. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The consequences of BVDV infection in heterologous hosts vary depending on the host- and virus-associated factors such as biotype, genotype, or antigenic variation. However, they are generally similar to those in cattle [ 9 - 11 ]. The typical clinical symptom of BVDV infection in goats is reproductive failure [ 7 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…The consequences of BVDV infection in heterologous hosts vary depending on the host- and virus-associated factors such as biotype, genotype, or antigenic variation. However, they are generally similar to those in cattle [ 9 - 11 ]. The typical clinical symptom of BVDV infection in goats is reproductive failure [ 7 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 71%
“…However, they are generally similar to those in cattle [ 9 - 11 ]. The typical clinical symptom of BVDV infection in goats is reproductive failure [ 7 , 11 , 12 ]. In the previous studies, natural BVDV infection in healthy goats was rarely reported, and the goats rarely became reinfected after recovery from infection.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…About 3 ml peripheral blood were collected from PARDS patients and healthy children. A total RNA blood kit (ThermoFisher, USA) was used to extract total RNA [ 20 ]. The concentration and purity of RNA have been detected by measuring their optical density (OD) 260 and OD 280 [ 21 ].…”
Section: Methodsmentioning
confidence: 99%